PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP KEPUASAN KERJA DALAM MENINGKATKAN KINERJA PEGAWAI RUMAH SAKIT PELAMONIA MAKASSAR - Aulia, Andi Besse Rezky; Ahri, Reza Aril; Mahmud, Nur Ulmy (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2024)
Health services are an effort to improve community welfare government priorities. Excellent health services are provided to support health improvement community as part of efforts to develop Indonesian society as a whole and as a whole. With a healthy society, people's quality of life will continue to improve, as will their resources Indonesia's human resources are able to compete with other countries. Therefore, the government provides a variety of support services to support the outlined programs and which is mandated for the successful development of public health. Behavior carried out outside of duty The main tasks carried out by officers in health facilities are usually called organizations citizenship behavior (OCB). OCB is behavior carried out by individuals that is not regulated by organization or agency and has no influence on the rewards to be obtained provide a positive impact on the company or agency if implemented well (Gunawan et al., 2019). OCB is a form of cooperation and a sense of shared responsibility to the agency or workplace. The aim of this research is to analyze the influence of influence Organizational Citizenship Behavior (OCB) on Job Satisfaction and Performance of Health Workers at PT Pelamonia Hospital Makassar. This type of research is analytical observational research with cross sectional study approach, with a sample size of 200 people, data analysis using tests multiple linear regression. The research results of the P value on the OCB variable include (Altruism, Conscientiousness, Sportsmanship, Courtesy, Civic Virtue) is smaller than the α value (0.05). There is There is no influence of OCB on job satisfaction and employee performance at Pelamonia Hospital Makassar OCB directly through satisfaction has an influence on the performance of Pelamonia Hospital employees Makassar.